2011
DOI: 10.1007/s11706-011-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Various fates of neuronal progenitor cells observed on several different chemical functional groups

Abstract: Neuronal progenitor cells cultured on gold-coated glass surfaces modified by different chemical functional groups, including hydroxyl ( -OH), carboxyl ( -COOH), amino ( -NH 2 ), bromo ( -Br), mercapto ( -SH), -Phenyl and methyl ( -CH 3 ), were studied here to investigate the influence of surface chemistry on the cells' adhesion, morphology, proliferation and functional gene expression. Focal adhesion staining indicated in the initial culture stage cells exhibited morphological changes in response to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These values were in accordance with previously published data. 16,18,19 The results indicated that the molecules were suitably self-assembled.…”
Section: Wettability Of the Surfaces By Water Contact Angle Measurementsmentioning
confidence: 94%
“…These values were in accordance with previously published data. 16,18,19 The results indicated that the molecules were suitably self-assembled.…”
Section: Wettability Of the Surfaces By Water Contact Angle Measurementsmentioning
confidence: 94%
“…Moreover, enhanced biological advantages can be achieved by tailoring the intrinsic characteristics of mesoporous silica nanostructures [26], such as porosity, functionalization [27,28], size [29], and shape. Specifically, it has been reported that rod-like shaped mesoporous silica nanoparticles are well suited for monitoring cell trafficking [30], and their hydrophilic character facilitates the adhesion and functioning of several brain cell types [31].…”
Section: Introductionmentioning
confidence: 99%